1977
DOI: 10.1111/j.1365-2133.1977.tb05187.x
|View full text |Cite
|
Sign up to set email alerts
|

A separation of clinical from epidermal thinning effect in the topical glucocorticoid clobetasone butyrate

Abstract: Clobetasone butyrate ointment has been shown to be more effective in treating psoriasis and eczema than flurandrenolone ointment yet to cause less epidermal thinning in a human experimental model. This is an indication that the clinical activity of topical glucocorticoids may not necessarily be inseparable from their propensity to cause atrophy of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Under occlusivc experimental conditions in normal subjects adrenal function suppression occurred with the non-fiuorinated hydrocortisone butyrate but not with the clobetasone butyrate wbich is fiuorinated. It has been shown that the number of halogen atoms is unrelated to a product's ability to produce side effects; clobetasol propionate contains the same number of halogen atoms as clobetasone butyrate but the former suppresses adrenal function (Allenby et ai, 1975;Staughton & August, 1975) and thins skin to a much greater extent than the latter (Munro & Wilson, 1975;Morley et aly 1976;Sparkcs, 1976;Winter & Wilson, 1976;Stevanovic et al, 1977;Dykes & Marks, 1977); tbe degree of atrophy caused by steroids is not necessarily directly related to their anti-inflammatory potency (Smith, Wchr & Chalkcr, 1976); fluorination is not necessary for potent anti-inflammatory effect (Stewart et aL, 1973;Young, Yoxall & Wagner, 1977); and we now show that fJuorination is not related to the ability to depress adrenal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under occlusivc experimental conditions in normal subjects adrenal function suppression occurred with the non-fiuorinated hydrocortisone butyrate but not with the clobetasone butyrate wbich is fiuorinated. It has been shown that the number of halogen atoms is unrelated to a product's ability to produce side effects; clobetasol propionate contains the same number of halogen atoms as clobetasone butyrate but the former suppresses adrenal function (Allenby et ai, 1975;Staughton & August, 1975) and thins skin to a much greater extent than the latter (Munro & Wilson, 1975;Morley et aly 1976;Sparkcs, 1976;Winter & Wilson, 1976;Stevanovic et al, 1977;Dykes & Marks, 1977); tbe degree of atrophy caused by steroids is not necessarily directly related to their anti-inflammatory potency (Smith, Wchr & Chalkcr, 1976); fluorination is not necessary for potent anti-inflammatory effect (Stewart et aL, 1973;Young, Yoxall & Wagner, 1977); and we now show that fJuorination is not related to the ability to depress adrenal function.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocortisone butyrate oi'X does not contain a halogen atom and published work suggested that it may have similar clinical activity to clobetasone butyrate 0-05",, which does contain halogens (Munro& Wilson, 1975;Morley, Fry & Walker, 1976;Stevanovic, Wilson & Sparkes, 1977;Polano& Kaanar, 1973;Takino & Kobayashi, 1975;Yasuda, 1973). It was therefore of interest to compare the two preparations for efficacy and for the ability to affect the HPA axis following percutaneous absorption.…”
mentioning
confidence: 99%
“…In our study we chose clobetasol propionate as the strong preparation, because of its ability to rapidly resolve conditions, and clobetasone butyrate as the mild one, because of its reasonable efficacy combined with a low propensity to cause side-effects [12,17]. In many conditions it will be appro priate to all other combinations of steroid preparations with different strengths and properties.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the insertion of a halogen atom in position 21 makes the translation 17-21 impossible, resulting in compounds like clobetasol (Stefanovic et al 1977) or mometasone (Shapiro et al 1987). This type of TC, however, is characterised by a higher degree of mineralocorticoid antiproliferative effects.…”
Section: Chemical Structure Of Topical Corticosteroidsmentioning
confidence: 99%